Perancangan Implementasi Tampilan Baru Web "Sambat" Kota Malang menggunakan Metode Design Thinking - Veby Angelia Ropita Turnip; Herman Tolle; Dwi Cahya Astriya Nugraha (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Living in the current era of information technology development provides convenience in various fields, for example in the field of technology. The Malang City Government applies the smart city concept, one example is a website that develops the smart city concept, namely Sambat Online. Sambat Online is a facility provided by the City Government of Malang to accommodate aspirations, suggestions, criticisms, complaints, and questions about Malang City. From the data obtained from Sambat Online statistics, it can be concluded that more people use SMS Sambat than accessing the Sambat Website. To get a good website, good user experience is also needed. For that one method that can be used is design thinking. Design thinking is an approach that provides solutions to solve problems directly, so that the solution to user problems is to create a new web appearance that is more attractive and easier to use. There are five stages in the design thinking method, namely Empathy, Define, Ideate, Prototype, and Test. In this study using data taken from 10 informants who are domiciled in Malang City and using usability tasting testing using 3 aspects of testing namely efficiency, effectiveness, and satisfaction. The results obtained from the effectiveness aspect are 100%, the efficiency aspect gets time-based efficiency which is 0.203 gaols/sec, and the satisfaction aspect is 88 which can be seen in the SUS value table getting a very good grade, as well as from the calculations obtained using the UEQ method, the results show that respondents prefer the new look of the splice website.